FORMULASI SEDIAAN KRIM LULUR KOPI ARABIKA (Coffea arabica) SEBAGAI ANTI-AGING - Vivi Purwandari; Maringan Silitonga; Cut Masyithah Thaib; Isra Kristina Sitohang (Jurnal Farmanesia, 2018)
Coffee is one of the plantation commodities that has a fairly high economic value among other plantation crops and plays an important role as a source of foreign exchange for the country. Coffee contains important compounds such as antioxidants and caffeine which functions as anti-aging so that it can be used as an anti-aging ingredient in the form of a scrub. The purpose of this study was to determine whether coffee can be formulated in the form of cream as an anti-aging, and in the form of a body scrub cream. The research method using experimental includes the collection of Arabica coffee ingredients, making formulations of Arabica coffee scrub cream preparations, and description of the quality of Arabica coffee cream body scrub preparations. Data analysis in this study used descriptive analysis by presenting the frequency distribution table of each study. The results of the study found that the difference in the concentration of Arabica coffee (Coffea arabica) in body scrub cream preparations had an effect with the best concentration of 15% compared to 5%, 10%, and blank concentrations, and the use of body scrub cream preparations containing Arabica coffee. (Coffea arabica) 15% showed improvement in skin condition for the better, during four weeks of treatment. Thus, Arabica coffee (Coffea arabica) can be formulated in the form of body scrub cream as anti-aging.